Efektivitas Praktik Kerja Industri dan Bimbingan Karir Terhadap Kesiapan Kerja Siswa dengan Mediasi Motivasi Kerja - Utami, Rahayu Siwi; Harsono, Harsono (Universitas Negeri Padang, 2025)
This study examines the impact of the interaction of industrial work practice and career guidance on students' work preparation with work motivation as a mediating variable. Using a quantitative survey design, data were collected through a Google Forms questionnaire on 85 students of class XII SMK Negeri 6 Surakarta who were selected by proportional random sampling. Structural Equation Modeling (SEM) analysis with the Partial Least Squares (PLS) approach through SmartPLS 4.0 shows that industrial work practice and career guidance significantly improve students' work readiness. Work motivation acts as a full mediator, strengthening the relationship between the two independent variables and the ability of students to face the demands of the labor market. The results of this study indicate that the success of vocational education is highly dependent on the synergy between hands-on experience in the world of work and structured career guidance support. Work motivation is an important psychological factor in connecting the learning process with actual readiness in the workplace. The findings confirm the importance of integrating industrial internship programs and motivation-based career counseling in the vocational education curriculum to improve graduate competitiveness. This research provides a practical contribution to the development of learning strategies that are responsive to industry dynamics.